A Study to Explore the Perception and Awareness on Islamic Banking Among College Students in the Province of Lanao Del Sur, Philippines - Jawad Z. Salic; Anwar Radiamoda; Shahid Manalundong; Abdulcader Ayo (Indonesian Journal of Banking and Financial Technology, 2023)
This exploration was conducted to examine the level of awareness and perception of individuals who are candidates for graduation for a bachelor's degree from the province of Lanao del Sur. A survey was conducted through a guided questionnaire to collect the insight of selected respondents to weigh their awareness and perception. This study aimed to assess the respondents' knowledge level of Islamic Banking after the creation of the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM). The study result showed that the respondents need integration on their journey of being a college students on Islamic Banking. The need for academic study among the respondents is highly recommended to the point that they are the successor of the present leader of BARMM. The study suggests a conception of an intervention program that will be conducted by other nations which are well-experienced in Islamic Banking.